Nature conservation in Polish agriculture under conditions of EU membership - Karol Kociszewski (Economic and Environmental Studies (E&ES), 2014)
The aim of the paper is to assess the effectiveness of the implementation of EU nature conservation measures in Polish agriculture. Environmental regulations influence main groups of Common Agricultural Policy instruments. In the Pillar I of the policy, this refers to cross-compliance, while in Pillar II this refers to agri-environmental programmes, the Natura 2000 payments and organic farming support. The implementation is ineffective and insufficiently directed to nature conservation. Domestic environmental and agricultural policy are not coordinated in all aspects. This is related to delay in construction of protection plans which are necessary for proper policy in the Natura 2000 network. Consequently, the specialized payments for farmers in the Natura 2000 network have not been implemented yet and agri-environmental measures have been implemented only partially. Moreover, the system of control and certification in organic farming does not involve requirements referring to biodiversity. There are some deficiencies in biodiversity protection standards within domestic regulations of cross-compliance. In this situation, Polish agriculture could contribute to degradation of biological diversity in rural areas.
Keywords: 330; environmental protection in agriculture; biodiversity; sustainable agricultural development; agri-environmental programmes; rural development measures